Trace element and Sr-Nd-Pb isotope geochemistry of Rungwe Volcanic Province, Tanzania: implications for a Superplume source for East Africa Rift magmatism - Castillo, Paterno R.; Hilton, David R.; Halldórsson, Sæmundur A. (Frontiers in Earth Science, 2014)
The recently-discovered high, plume-like 3He/4He ratios at Rungwe Volcanic Province (RVP) in southern Tanzania, similar to those at the Main Ethiopian Rift in Ethiopia, strongly suggest that magmatism associated with continental rifting along the entire East African Rift System (EARS) has a deep mantle contribution (Hilton et al., 2011). New trace element and Sr-Nd-Pb isotopic data for high 3He/4He lavas and tephras from RVP can be explained by binary mixing relationships involving Early Proterozoic (±Archaean) lithospheric mantle, present beneath the southern EARS, and a volatile-rich carbonatitic plume with a limited range of compositions and best represented by recent Nyiragongo lavas from the Virunga Volcanic Province also in the Western Rift. Other lavas from the Western Rift and from the southern Kenyan Rift can also be explained through mixing between the same endmember components. In contrast, lavas from the northern Kenyan and Main Ethiopian rifts can be explained through variable mixing between the same mantle plume material and Middle to Late Proterozoic lithospheric mantle, present beneath the northern EARS. Thus, we propose that the bulk of EARS magmatism is sourced from mixing among three endmember sources: Early Proterozoic (±Archaean) lithospheric mantle, Middle to Late Proterozoic lithospheric mantle and a volatile-rich carbonatitic plume with a limited range of compositions. We propose further that the African Superplume, a large, seismically anomalous feature originating in the lower mantle beneath southern Africa, influences magmatism throughout eastern Africa with magmatism at RVP and the Main Ethiopian Rift representing two different heads of a single mantle plume source. This is consistent with a single mantle plume origin of the coupled He-Ne isotopic signatures of mantle-derived xenoliths and/or lavas from all segments of the EARS (Halldórsson et al., 2014).